The suppression of fluorescence peaks in energy‐dispersive X‐ray diffraction. (1st October 2014) - Hansford, G. M.; Turner, S. M. R.; Staab, D.; Vernon, D.
<x xml:space="preserve">Abstract</x> A novel method to separate diffraction and fluorescence peaks in energy‐dispersive X‐ray diffraction (EDXRD) is described. By tuning the excitation energy of an X‐ray tube source to just below an elemental absorption edge, the corresponding fluorescence peaks of that element are completely suppressed in the resulting spectrum. Since Bremsstrahlung photons are present in the source spectrum up to the excitation energy, any diffraction peaks that lie at similar energies to the suppressed fluorescence peaks are uncovered. This technique is an alternative to the more usual method in EDXRD of altering the scattering angle in order to shift the energies of the diffraction peaks. However, in the back‐reflection EDXRD technique [Hansford (2011). J. Appl. Cryst.44, 514–525] changing the scattering angle would lose the unique property of insensitivity to sample morphology and is therefore an unattractive option. The use of fluorescence suppression to reveal diffraction peaks is demonstrated experimentally by suppressing the Ca K fluorescence peaks in the back‐reflection EDXRD spectra of several limestones and dolomites. Three substantial benefits are derived: uncovering of diffraction peak(s) that are otherwise obscured by fluorescence; suppression of the Ca K escape peaks; and an increase in the signal‐to‐background ratio. The improvement in the quality of the EDXRD spectrum allows the identification of a secondary mineral in the samples, where present. The results for a pressed‐powder pellet of the geological standard JDo‐1 (dolomite) show the presence of crystallite preferred orientation in this prepared sample. Preferred orientation is absent in several unprepared limestone and dolomite rock specimens, illustrating an advantage of the observation of rocks in their natural state enabled by back‐reflection EDXRD.